2012
DOI: 10.1093/bja/aes146
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebrospinal fluid magnesium levels in patients undergoing spinal anaesthesia for hip arthroplasty: does intravenous infusion of magnesium sulphate make any difference? A prospective, randomized, controlled study

Abstract: Spinal anaesthesia unexpectedly reduced CSF total and ionized Mg concentrations in patients undergoing hip arthroplasty, although the mechanism is unclear. The dose used for peripheral MgSO(4) infusion in this study had no influence on central Mg concentrations in neurologically healthy patients undergoing spinal anaesthesia. If CSF Mg concentration is a reliable marker of Mg brain bioavailability, peripherally infused MgSO(4) during spinal anaesthesia is unlikely to influence central NMDA receptor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
4
11
0
1
Order By: Relevance
“…Recent reviews of the literature in humans showed that intrathecal magnesium does allow for an interesting decrease in postoperative acute pain, 50 but intravenous magnesium was less potent. 51 The fact that intravenous magnesium was less convincing to decrease acute postoperative pain might be explained by one clinical trial from Mercieri et al 52 In their study, the authors reported that intravenous magnesium did not properly cross the blood-brain barrier and, thus, could hardly be expected to decrease acute postoperative pain if this effect relied on its activity at the CNS level. Regarding PPSP, there is a lack of studies evaluating the impact of magnesium on such long-term outcome.…”
Section: Ketaminementioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of the literature in humans showed that intrathecal magnesium does allow for an interesting decrease in postoperative acute pain, 50 but intravenous magnesium was less potent. 51 The fact that intravenous magnesium was less convincing to decrease acute postoperative pain might be explained by one clinical trial from Mercieri et al 52 In their study, the authors reported that intravenous magnesium did not properly cross the blood-brain barrier and, thus, could hardly be expected to decrease acute postoperative pain if this effect relied on its activity at the CNS level. Regarding PPSP, there is a lack of studies evaluating the impact of magnesium on such long-term outcome.…”
Section: Ketaminementioning
confidence: 99%
“…51 Le fait que le magnésium intraveineux s'avère moins efficace pourrait être expliqué par une étude de Mercieri et coll. 52 Dans cet article, les auteurs rapportent que le magnésium intraveineux ne traverse pas correctement la barrière hémato-méningée. Il ne pourrait ainsi atteindre la cible souhaitée pour l'effet analgésique recherché, soit le niveau central spinal.…”
Section: Kétamineunclassified
“…There is evidence that NMDA-receptor exists in the peripheral terminal of articular primary afferent fibers and cellular elements of the joint (25). Previous studies revealed that magnesium exerted its possible anti-nociceptive effect predominantly via peripheral NMDA-receptor mechanisms when administrated locally (26)(27)(28). Therefore, the method of intra-articular injection was adopted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these studies (3-5), in our study, pre-eclamptic patients received MgSO 4 before spinal anaesthesia and the lowest total dose of magne- One major problem with systemic magnesium administration is the bioavailability of magnesium to the central nervous system (CNS). The brain concentration of magnesium, reflected by the CSF magnesium concentration, is tightly controlled in healthy subjects (19) and in disease states such as acute traumatic injury (14). Magnesium has also been applied neuraxially to avoid the poor passage into CNS following systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…There are two studies (7,19) that evaluated CSF magnesium levels following IV magnesium administration, only one of which investigated postoperative analgesic consumption. Ko et al (7) administered magnesium doses that were 50-70% of the pre-eclampsia treatment for a shorter period of time (6 hours) in non-obstetric patients receiving general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%